The Role of Social Media in Online Marketing of Halal Products - Pratama, Arya; Ditya, Nabila (FEBI UIN Sunan Kalijaga, 2023)
This study undertakes a descriptive analysis focused on elucidating the pivotal role of social media in the realm of online business marketing. The primary goal is to furnish valuable insights and practical guidance for internet users engaging in the marketing of their online businesses through the utilization of social media platforms. The chosen research methodology for this study is descriptive qualitative. This method is particularly well-suited for accommodating the myriad influences on value patterns, presenting data in the form of words and image. The findings of this research endeavor are anticipated to offer a nuanced understanding of the dynamics at play, shedding light on the various dimensions of leveraging social media effectively for halal online business marketing. Ultimately, the study aspires to equip halal business practitioners with actionable insights to enhance their online marketing endeavors in the ever-evolving landscape of social media